2019
DOI: 10.1073/pnas.1817222116
|View full text |Cite
|
Sign up to set email alerts
|

Structural maturation of cortical perineuronal nets and their perforating synapses revealed by superresolution imaging

Abstract: Parvalbumin-positive (PV+) interneurons play a pivotal role in orchestrating windows of experience-dependent brain plasticity during development. Critical period closure is marked by the condensation of a perineuronal net (PNN) tightly enwrapping subsets of PV+ neurons, both acting as a molecular brake on plasticity and maintaining mature PV+ cell signaling. As much of the molecular organization of PNNs exists at length scales near or below the diffraction limit of light microscopy, we developed a superresolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 45 publications
3
90
0
Order By: Relevance
“…Interestingly, we found that additional changes occur specifically to PV+ in the auditory cortex of heterozygous Mecp2 mutants (MeCP2 het ), namely increased expression of parvalbumin and intensification of perineuronal nets (PNNs). PNNs are glycoprotein structures in the extracellular matrix surrounding PV+ that act as physical barriers to or modulators of synaptic modifications, and actively control maturation of PV+ (Krishnan et al, 2015;Sorg et al, 2016;Miyata and Kitagawa, 2017;Sigal et al, 2019). Thus, PNNs are proposed to work in concert with elevated parvalbumin to act as 'brakes' on plasticity e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found that additional changes occur specifically to PV+ in the auditory cortex of heterozygous Mecp2 mutants (MeCP2 het ), namely increased expression of parvalbumin and intensification of perineuronal nets (PNNs). PNNs are glycoprotein structures in the extracellular matrix surrounding PV+ that act as physical barriers to or modulators of synaptic modifications, and actively control maturation of PV+ (Krishnan et al, 2015;Sorg et al, 2016;Miyata and Kitagawa, 2017;Sigal et al, 2019). Thus, PNNs are proposed to work in concert with elevated parvalbumin to act as 'brakes' on plasticity e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The interneurons have complex dendritic arborization to regulate the activity of principal neurons. PNN has an indirect role over principal neurons via regulating synaptic plasticity (Sigal et al, 2019) and dendritic arborization (Stolp et al, 2019) of the interneuron. In addition, PNN plays a key role in retaining neuronal connectivity (Bikbaev et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…show that earlier in development, PNNs have greater structural heterogeneity (Sigal et al, 2019). This structural heterogeneity could necessitate larger data sets at the ages where PNNs are in the process of forming.…”
Section: Recent Work By Sigal Et Al Used a Stochastic Optical Reconsmentioning
confidence: 99%